MUSIKALISCHE AUSGESTALTUNG DES GOTTESDIENSTES AM 1. SONNTAG NACH TRINITATIS - NACH DER G1 ORDNUNG IN BAYERN - - MOLNÁR, Zsuzsánna (Studia Universitatis Babes-Bolyai Musica, 2017)
Musical Framework for the Divine Service on the 1st Trinity Sunday - According to the G1 Arrangement in Bavaria. The choir play a very important role in the German Evangelic church service and in the liturgy. It can be present in the church service as an independent musical part or as the substitute of the liturgy. Choral music can be just an opening or an ending part of the church service but it also can be an essential part of the liturgy by helping the congregation accompanying it. The topics of the musical pieces sung by the choir are related to the weekly psalm or to the sermon (told by the minister). The dynamic of the actual church service and the role of the choir in it are based on an agreement between the minister and the choir’s conductor. The essay that can be read below demonstrates the double role of the choir in the church service. In the “Kyrie” and the ”Gloria” parts it is giving an answer to the recitation song. In the choral piece “Der Herr ist mein Hirt” it is presented as a personal credo for the sermon’s message. At the ending of the church service Luther Martin’s words are spoken in the elaboration of Bartholdy F. M. (the 500th anniversary of the Reformation/ 2017): „Give us peace with grace”.